Highest and Best Use for Mall’s Motorcycle Parking Area Surabaya - Rafael Dani Kusuma; Christiono Utomo (Institut Teknologi Sepuluh Nopember, 2020)
Property growth for residence, office building, and other uses is increasingly higher. This results in the development plan for a land that can change along with changes in its surroundings. Therefore, an analysis is needed to determine the utilization of land so that it can produce alternative properties with the highest income and land value. This research uses the Highest and Best Use (HBU) method to analyze Tunjungan Plaza parking area to the best and highest use of a land which was originally a parking lot. This research begins with an analysis of land development trends around the location and the respondent/stakeholders analysis through questionnaire and interview techniques to formulate which type of property and development that will be analyzed by the Highest and Best Use method. From the results from the identification of alternative land uses, five alternative developments using the mixed-use building consisting of apartment-hotel and office-apartment systems were obtained. From the results of the analysis conducted, the highest value of land productivity was obtained by developing land with mixeduse building system which consists apartment (50%) - hotels (50%) that gives enhancement the land value of Rp. 463.051.849, - / m2 or an increase of 1.267,25 % from before development was conducted.